Kinerja KPU Kota Blitar Dalam Meningkatkan Partisipasi Pemilih Pada Pemilihan Gubernur Dan Wakil Gubernur Jawa Timur Tahun 2018 - Pristiko Gunawan (Universitas Islam Kadiri, 2020)
The direct election of the Governor and Deputy Governor is the implementation of the mandate of the law, this study has the aim to determine the extent of the performance of the KPU Blitar City in increasing voter participation in the election of the Governor and Deputy Governor of East Java in 2018. There are various problems which includehuman resources from KPU has not been optimal in the level of village government and sub-district government, and lack of participation from the community due to factors of economic interests, domiciles in the outer areas of Blitar City, and lack of public awareness. The performance theory proposed by Mahsun (2012: 77) is used as a theoretical basis. The object of the research was the Blitar City KPU, carried out through a qualitative approach using interview methods and using secondary data in the form of literature studies from several scientific references suitable for following up the analysis of primary data obtained. The results of the study illustrate that the performance of the Blitar City KPU in the election of the Governor and Deputy Governor of East Java in 2018 cannot be said to be optimal. Because there are still obstacles to the Blitar City Election Commission in increasing voter participation which is seen from the indicators of input, process, results and impact.